Association between overweight and obesity in schoolchildren with rs9939609 polymorphism (FTO) and family history for obesity - Cézane Priscila Reuter; Miria Suzana Burgos; Joana Carolina Bernhard; Debora Tornquist; Elisa Inês Klinger; Tássia Silvana Borges; Jane Dagmar Pollo Renner; Andréia Rosane de Moura Valim; Elza Daniel de Mello
Abstract Objective: To determine the association between overweight/obesity in schoolchildren with FTO rs9939609 polymorphism (fatmass and obesity associated) and family history of obesity. Methods: Cross-sectional study comprising a sample of 406 children aged 7-17 years in a city in southern Brazil. Overweight/obesity in schoolchildren was assessed by body mass index (BMI), and family history of obesity was self-reported by parents. Polymorphism genotyping was performed by real time PCR (polymerase chain reaction). The association between the nutritional status of schoolchildren with the presence of family obesity, stratified by polymorphism genotypes (AA [at-risk for obesity], AT, and TT), was assessed by prevalence ratio values (PR) through Poisson regression. Results: Among schoolchildren with the AA genotype, 57.4% had overweight/obesity; the percentage was lower for the AT and TT genotypes (33.1% and 28.9%, respectively). Overweight/obesity in schoolchildren was associated with a family history of obesity, especially among children with the AA genotype. The prevalence was higher among those with an obese mother (PR: 1.28; p < 0.001), obese maternal or paternal grandmother (PR: 1.22; p = 0.047), and obese paternal grandfather (PR: 1.32; p < 0.001). Conclusions: There is an association between the AA genotype of rs9939609 polymorphism and BMI among schoolchildren. The association between overweight/obesity in schoolchildren with a family history of obesity was found mainly among students with the AA genotype.